DNA and its Metaphors - Domaradzki, Jan (Respectus Philologicus, 2015)
The aim of the present paper is to describe the main metaphors presented in genetic discourse: DNA as text, information, language, book, code, project/blueprint, map, computer, music, and cooking. It also analyses the social implication of these metaphors. The author of this article argues that metaphors are double-edged swords: while they brighten difficult and abstract genetic concepts, they also lead to the misunderstanding and misinterpretation of the reality. The reason for this is that most of these metaphors are of deterministic, reductionist, and fatalistic character. Consequently, they shift the attention from complexity of genetic processes. Moreover, as they appeal to emotions, ascetics, and morality they may involve exaggeration: while they bring hope, they also create an atmosphere of fear over the misuse of genetic knowledge. The author of this article states that the genetic metaphors do not simply reflect the social ideas on DNA, but also shape our understanding of genetics and imagination on the social application of genetic knowledge. Due to this reason, DNA should be understood not only as a biological code, but as a cultural as well.